Enhanced targeted treatment of cervical cancer using nanoparticle-based doxycycline delivery system - Sadia Anjum; Ayesha Akhtar; Saleh M. Aldaqal; Maisa S. Abduh; Hammad Ahmad; Riaz Mustafa; Faiza Naseer; Maryam Sadia; Tahir Ahmad (Scientific Reports)
Abstract This study investigates a nanoparticle-based doxycycline (DOX) delivery system targeting cervical cancer cells via the CD44 receptor. Molecular docking revealed a strong binding affinity between hyaluronic acid (HA) and CD44 (binding energy: -7.2 kJ/mol). Characterization of the HA-Chitosan nanoparticles showed a particle size of 284.6 nm, a zeta potential of 16.9 mV, and a polydispersity index of 0.314, with SEM confirming smooth surface morphology. The encapsulation efficiency of DOX-loaded nanoparticles was 89.32%, exhibiting a sustained release profile, with 67.45% released over 72 h in acidic conditions (pH 5.5). Cytotoxicity assays demonstrated a significant reduction in HeLa cell viability to 22% at 72 h, compared to 67% in normal HEK cells. Stability tests confirmed the maintenance of nanoparticle integrity and a consistent drug release profile over three months. Cell migration was reduced by 45%, and RT-PCR analysis revealed a 53% downregulation of TNF-α expression, suggesting effective targeting of inflammatory pathways. These results underscore the potential of HA-Chitosan-based DOX nanoparticles in improving cervical cancer treatment through enhanced targeted delivery and inhibition of tumor-promoting mechanisms.